Polyamide 12 / modified boron nitride composite powder as well as preparation method and application thereof

Boron nitride was peeled off into nanosheets and modified into hydroxylated boron nitride through high-pressure homogenization technology, which solved the problem of slow cooling rate and poor dispersion of boron nitride during the preparation process, and achieved efficient preparation and performance improvement of polyamide 12/modified boron nitride composite powder.

CN119592058APending Publication Date: 2025-03-11GUIZHOU MATERIAL IND TECH INSTITUE
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411908533.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

The existing polyamide 12 powder has slow cooling rate, high energy consumption during the preparation process, and poor dispersion after blending with boron nitride, resulting in limited performance improvement.

Method used

Boron nitride is peeled off into boron nitride nanosheets through high-pressure homogenization technology, and a dispersant containing hydroxyl groups is introduced, and it is modified to hydroxylated boron nitride to improve its dispersion and compatibility with polyamide 12.

Benefits of technology

The modified boron nitride is uniformly dispersed in the polyamide 12 powder, which improves the thermal conductivity and sintering properties of the powder, enhances the mechanical properties and spherical shape, and is simple and easy to industrialize.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119592058A_ABST
    Figure CN119592058A_ABST
Patent Text Reader

Abstract

The invention provides polyamide 12 / modified boron nitride composite powder as well as a preparation method and application thereof, and belongs to the technical field of high polymer materials. Boron nitride is stripped into boron nitride nanosheets by utilizing high-pressure homogeneous impact force, shearing force and hole effect, a dispersing agent rich in hydroxyl groups is introduced into the boron nitride to modify the boron nitride into hydroxylated boron nitride, and the dispersity and compatibility among the modified boron nitride, polyamide 12 liquid drops and a solvent are obviously improved; the prepared composite powder has good sphericity, narrow particle size distribution and excellent mechanical properties, and can be well applied to powder materials for selective laser sintering.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polymer materials, and specifically relates to a polyamide 12 / modified boron nitride composite powder and a preparation method and application thereof. Background Art

[0002] Selective laser sintering (SLS) technology uses the thermal effect of high-power lasers to selectively irradiate and solidify powder materials layer by layer. Compared with traditional processes, SLS does not require additional support structures, and the unsintered powder can directly support the suspended layers that appear during the lamination process, effectively improving material utilization and diversifying molding materials. Therefore, it is widely used in aerospace, machinery, electronics, biomedicine and other fields. Polyamide 12 powder has become the most widely used 3D printing material due to its good mechanical properties, thermal stability and printing quality.

[0003] In the related art, patent CN111171345A controls the sphericity of polyamide 12 powder by setting two stages of cooling, and the slowest cooling rate is only 0.05°C / min, which takes a long time to prepare and consumes a lot of energy, which is not conducive to industrial production. Patent CN116355397A improves the processing performance of polyamide 12 powder by blending thermoplastic elastomer and heat-resistant filler in polyamide 12 powder, but directly blending filler easily makes the powder uneven, resulting in poor powder spreading effect.

[0004] Boron nitride has good machinability, lubricity, thermal stability, chemical stability and thermal conductivity. Strengthening polyamide 12 by blending boron nitride is an important way to further improve the performance of polyamide 12. However, due to the stable physicochemical properties of boron nitride and the almost no functional groups on the surface, its dispersion effect is poor and it is easy to form agglomerates. In addition, the mechanical strength and thermal conductivity of unstripped boron nitride are much worse than those of stripped boron nitride. This results in the performance of polyamide 12 / boron nitride composite powder being not much different from that of polyamide 12 powder.

[0005] Therefore, it is necessary to provide a polyamide 12 / modified boron nitride composite powder and a preparation method and application thereof to solve the above problems. Summary of the invention

[0006] The present invention provides a polyamide 12 / modified boron nitride composite powder, a preparation method and application thereof. Boron nitride is modified to improve the dispersibility and compatibility between boron nitride and polyamide 12 droplets and solvents. The prepared composite powder has good sphericity, narrow particle size distribution, and excellent mechanical properties of the product, which can effectively solve at least one technical problem involved in the background technology.

[0007] In order to solve the above-mentioned technical problems, the present invention is achieved as follows:

[0008] A method for preparing a polyamide 12 / modified boron nitride composite powder comprises the following steps:

[0009] Step S1, taking 5-15 parts of boron nitride, 5-15 parts of a dispersant containing a hydroxyl group, and 70-90 parts of a first solvent by weight and performing high-pressure homogenization to exfoliate the boron nitride into boron nitride nanosheets to obtain a hydroxylated boron nitride emulsion;

[0010] Step S2, adding 5-15 parts of polyamide 12 pellets and 75-92 parts of the second solvent into a reaction kettle according to weight proportions, heating at a certain temperature and stirring evenly to obtain a uniform solution;

[0011] Step S3, adding 3-10 parts by mass of the hydroxylated boron nitride emulsion obtained in step S1 to the uniform solution obtained in step S2, and stirring sufficiently to make the hydroxylated boron nitride emulsion uniformly dispersed in the solution;

[0012] Step S4, cooling the solution obtained in step S3 according to a program to form a suspension, filtering the suspension and washing it with deionized water to remove the solvent, and drying to obtain a polyamide 12 / modified boron nitride composite powder.

[0013] As a preferred improvement, in step S1, the dispersant is selected to be at least one of carboxymethyl cellulose and hydroxypropyl cellulose; and the first solvent is selected to be at least one of N,N-dimethylformamide and N,N-dimethylacetamide.

[0014] As a preferred improvement, in step S1, the homogenization pressure during the high-pressure homogenization process is 50-200 bar, and the homogenization time is 5-15 min.

[0015] As a preferred improvement, in step S2, the heating temperature is 130-150°C, the stirring rate is 100-600 rpm, and the stirring time is 0.5-2h; the second solvent is selected from at least one of N,N-dimethylformamide and N,N-dimethylacetamide.

[0016] As a preferred improvement, in step S4, the cooling rate is 5-10°C / min, and the drying temperature is 60-80°C.

[0017] A polyamide 12 / modified boron nitride composite powder is prepared by adopting the above-mentioned method for preparing the polyamide 12 / modified boron nitride composite powder.

[0018] An application of the polyamide 12 / modified boron nitride composite powder is used as a powder material for selective laser sintering.

[0019] The beneficial effects of the present invention are:

[0020] (1) Boron nitride is exfoliated into boron nitride nanosheets by using the impact force, shear force and cavitation effect of high-pressure homogenization, and then a dispersant rich in hydroxyl groups is introduced into the boron nitride to convert it into hydroxylated boron nitride. The dispersibility and compatibility between the modified boron nitride and polyamide 12 droplets and solvents are significantly improved. The thermal conductivity of boron nitride is improved by modifying the boron nitride, which is beneficial to the conversion of laser radiation energy into effective heat during the laser sintering process, promoting heat transfer between powders and improving the sintering performance of the powders;

[0021] (2) The nucleation effect of boron nitride is utilized to make the polyamide 12 droplets in situ nucleate and coat the boron nitride, further improving the uniformity of boron nitride in the polyamide 12 powder;

[0022] (3) The preparation method of the present application has a simple preparation process and is easy to industrialize. The prepared composite powder has good sphericity and a narrow particle size distribution, and the prepared product has excellent mechanical properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative work, among which:

[0024] Figure 1 The optical image of the sample prepared in Example 1 is shown. DETAILED DESCRIPTION

[0025] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0026] This embodiment provides a method for preparing a polyamide 12 / modified boron nitride composite powder, comprising the following steps:

[0027] Step S1, taking 5-15 parts of boron nitride, 5-15 parts of a dispersant containing a hydroxyl group, and 70-90 parts of a first solvent by weight and performing high-pressure homogenization to exfoliate the boron nitride into boron nitride nanosheets to obtain a hydroxylated boron nitride emulsion.

[0028] The dispersant is selected from at least one of carboxymethyl cellulose and hydroxypropyl cellulose; the first solvent is selected from at least one of N,N-dimethylformamide and N,N-dimethylacetamide.

[0029] The high-pressure homogenization process is performed by a high-pressure homogenizer, with a homogenization pressure of 50-200 bar and a homogenization time of 5-15 minutes. The impact force, shear force and cavitation effect of high-pressure homogenization are used to peel off the boron nitride to make it into boron nitride nanosheets, and then a dispersant rich in hydroxyl groups is introduced into the boron nitride to modify it into hydroxylated boron nitride. The dispersibility and compatibility between the modified boron nitride and the polyamide 12 droplets and solvents are significantly improved. The thermal conductivity of boron nitride is improved by modifying the boron nitride, which is beneficial to the conversion of laser radiation energy into effective heat during the laser sintering process, promoting heat transfer between powders and improving the sintering performance of the composite powder.

[0030] Step S2, according to the mass fractions, 5-15 parts of polyamide 12 pellets and 75-92 parts of the second solvent are added into a reaction kettle, heated at a certain temperature and stirred evenly to obtain a uniform solution.

[0031] In step S2, the heating temperature is 130-150°C, and the stirring speed is 100-600 rpm. The second solvent is selected from at least one of N,N-dimethylformamide and N,N-dimethylacetamide.

[0032] Step S3, taking 3-10 parts by mass of the hydroxylated boron nitride emulsion obtained in step S1 and adding them to the uniform solution obtained in step S2, and stirring them sufficiently to make the hydroxylated boron nitride emulsion uniformly dispersed in the solution.

[0033] In step S3, the stirring time is 0.5-2h.

[0034] Step S4, cooling the solution obtained in step S3 according to a program to form a suspension, filtering the suspension and washing it with deionized water to remove the solvent, and drying to obtain a polyamide 12 / modified boron nitride composite powder.

[0035] By utilizing the nucleation effect of boron nitride, polyamide 12 droplets are in-situ nucleated to coat boron nitride, further improving the uniformity of boron nitride in polyamide 12 powder.

[0036] In step S4, the cooling rate is 5-10°C / min and the drying temperature is 60-80°C.

[0037] This embodiment also provides a polyamide 12 / modified boron nitride composite powder, which is prepared by the above-mentioned method for preparing the polyamide 12 / modified boron nitride composite powder.

[0038] This embodiment also provides an application of polyamide 12 / modified boron nitride composite powder, which is used as a powder material for selective laser sintering.

[0039] Example 1

[0040] Homogenize 8 parts of boron nitride, 8 parts of carboxymethyl cellulose and 84 parts of N,N-dimethylformamide at a pressure of 100 bar for 12 minutes to obtain a hydroxylated boron nitride emulsion; then weigh 7 parts of polyamide 12 pellets and 85 parts of N,N-dimethylformamide and add them to a reactor, mix them evenly at a stirring rate of 500 rpm at 145°C to obtain a uniform solution; add 8 parts of hydroxylated boron nitride emulsion to the obtained uniform solution, stir it thoroughly at a stirring rate of 500 rpm for 1 hour to evenly disperse the hydroxylated boron nitride emulsion in the solution; then cool it to 80°C at a cooling rate of 5°C / min to take out the suspension. Filter the suspension and wash it thoroughly with deionized water to remove the solvent, and dry it at 70°C to obtain a polyamide 12 / modified boron nitride composite powder sample. The optical image of the sample prepared in Example 1 is as follows Figure 1 As shown, from Figure 1 It can be seen that the prepared powder has good sphericity and narrow particle size distribution, and boron nitride is uniformly dispersed in polyamide 12.

[0041] Example 2

[0042] 10 parts of boron nitride, 10 parts of carboxymethyl cellulose, and 80 parts of N,N-dimethylacetamide were homogenized at a pressure of 120 bar for 15 minutes to obtain a hydroxylated boron nitride emulsion; then 5 parts of polyamide 12 pellets and 88 parts of N,N-dimethylformamide were weighed and added to the reactor, and mixed evenly at a stirring rate of 500 rpm at 145°C to obtain a uniform solution; 7 parts of hydroxylated boron nitride emulsion were added to the obtained uniform solution, and stirred at a stirring rate of 500 rpm for 1 hour to make the hydroxylated boron nitride emulsion evenly dispersed in the solution; then the suspension was cooled to 80°C at a cooling rate of 7°C / min to take out the suspension. The suspension was filtered and washed with deionized water to remove the solvent, and dried at 70°C to obtain a polyamide 12 / modified boron nitride composite powder sample.

[0043] Example 3

[0044] 8 parts of boron nitride, 8 parts of hydroxypropyl cellulose and 84 parts of N,N-dimethylformamide were homogenized at a pressure of 100 bar for 12 minutes to obtain a hydroxylated boron nitride emulsion; then 7 parts of polyamide 12 pellets and 85 parts of N,N-dimethylacetamide were weighed and added to the reactor, and mixed evenly at a stirring rate of 500 rpm at 150°C to obtain a uniform solution; 5 parts of hydroxylated boron nitride emulsion were added to the obtained uniform solution, and stirred at a stirring rate of 500 rpm for 1 hour to make the hydroxylated boron nitride emulsion evenly dispersed in the solution; then the suspension was cooled to 80°C at a cooling rate of 5°C / min to take out the suspension. The suspension was filtered and washed with deionized water to remove the solvent, and dried at 70°C to obtain a polyamide 12 / modified boron nitride composite powder sample.

[0045] Example 4

[0046] 12 parts of boron nitride, 12 parts of hydroxypropyl cellulose, and 76 parts of N,N-dimethylacetamide were homogenized at a pressure of 150 bar for 15 minutes to obtain a hydroxylated boron nitride emulsion; then 5 parts of polyamide 12 pellets and 90 parts of N,N-dimethylacetamide were weighed and added to the reactor, and mixed evenly at a stirring rate of 500 rpm at 150°C to obtain a uniform solution; 5 parts of hydroxylated boron nitride emulsion were added to the obtained uniform solution, and stirred at a stirring rate of 500 rpm for 1 hour to uniformly disperse the hydroxylated boron nitride emulsion in the solution; then the suspension was cooled to 80°C at a cooling rate of 6°C / min to take out the suspension. The suspension was filtered and fully washed with deionized water to remove the solvent, and dried at 70°C to obtain a polyamide 12 / modified boron nitride composite powder sample.

[0047] Comparative Example 1

[0048] Weigh 7 parts of polyamide 12 pellets and 93 parts of N,N-dimethylformamide into a reactor, mix at 145°C and 500 rpm for 1 hour to obtain a uniform solution; then cool to 80°C at a cooling rate of 5°C / min to take out the suspension. Filter the suspension and wash it with deionized water to remove the solvent, and dry it at 70°C to obtain a polyamide 12 powder sample.

[0049] Comparative Example 2

[0050] Weigh 7 parts of polyamide 12 pellets, 1 part of boron nitride, and 93 parts of N,N-dimethylformamide into a reactor, mix at 145°C with a stirring rate of 500 rpm for 1 hour, then cool to 80°C at a cooling rate of 5°C / min to take out the suspension. Filter the suspension and wash it with deionized water to remove the solvent, and dry it at 70°C to obtain polyamide 12 / boron nitride powder.

[0051] The samples prepared in Examples 1-4 and Comparative Examples 1-2 were sintered using a selective laser sintering device to obtain products. The fracture strength and elongation of the products were measured. The performance data are shown in Table 1 below.

[0052] Table 1 Test data of the prepared sample parts of Examples 1-4 and Comparative Examples 1-2

[0053]

[0054] Comparing Comparative Example 1 with Comparative Example 2, it can be seen that the introduction of boron nitride can increase the tensile strength of the sample product to a certain extent, but the effect of improving the tensile modulus and elongation at break is not obvious, mainly due to the uneven distribution of boron nitride in the polyamide 12 matrix. Comparing Examples 1-4 with Comparative Examples 1-2, it can be seen that after the modified boron nitride is compounded with polyamide 12, the tensile strength, tensile modulus and elongation at break of the sample product are greatly improved, indicating that the modified boron nitride can be evenly distributed in the polyamide 12 matrix, and by forming a heat conduction channel and reducing the van der Waals force, the bonding performance between the two is optimized, thereby enhancing the overall mechanical properties of the polyamide 12 preparation.

[0055] The embodiments of the present invention are described above in conjunction with the accompanying drawings, but the present invention is not limited to the above-mentioned specific implementation modes, which are merely illustrative rather than restrictive. Under the guidance of the present invention, ordinary technicians in this field can also make many forms without departing from the scope of protection of the present invention and the claims, all of which are within the protection of the present invention.

Claims

1. A method for preparing a polyamide 12 / modified boron nitride composite powder, characterized in that: The steps include: Step S1, taking 5-15 parts of boron nitride, 5-15 parts of a dispersant containing a hydroxyl group, and 70-90 parts of a first solvent by weight and performing high-pressure homogenization to exfoliate the boron nitride into boron nitride nanosheets to obtain a hydroxylated boron nitride emulsion; Step S2, adding 5-15 parts of polyamide 12 pellets and 75-92 parts of the second solvent into a reaction kettle according to weight proportions, heating at a certain temperature and stirring evenly to obtain a uniform solution; Step S3, adding 3-10 parts by mass of the hydroxylated boron nitride emulsion obtained in step S1 to the uniform solution obtained in step S2, and stirring sufficiently to make the hydroxylated boron nitride emulsion uniformly dispersed in the solution; Step S4, cooling the solution obtained in step S3 according to a program to form a suspension, filtering the suspension and washing it with deionized water to remove the solvent, and drying to obtain a polyamide 12 / modified boron nitride composite powder.

2. The method for preparing the polyamide 12 / modified boron nitride composite powder according to claim 1, characterized in that: In step S1, the dispersant is selected to be at least one of carboxymethyl cellulose and hydroxypropyl cellulose; the first solvent is selected to be at least one of N,N-dimethylformamide and N,N-dimethylacetamide.

3. The method for preparing the polyamide 12 / modified boron nitride composite powder according to claim 1, characterized in that: In step S1, the homogenization pressure during the high-pressure homogenization process is 50-200 bar, and the homogenization time is 5-15 minutes.

4. The method for preparing the polyamide 12 / modified boron nitride composite powder according to claim 1, characterized in that: In step S2, the heating temperature is 130-150°C, the stirring rate is 100-600 rpm, and the stirring time is 0.5-2h; the second solvent is selected from at least one of N,N-dimethylformamide and N,N-dimethylacetamide.

5. The method for preparing the polyamide 12 / modified boron nitride composite powder according to claim 1, characterized in that: In step S4, the cooling rate is 5-10°C / min, and the drying temperature is 60-80°C.

6. A polyamide 12 / modified boron nitride composite powder, characterized in that: The polyamide 12 / modified boron nitride composite powder is prepared by the preparation method of any one of claims 1 to 5.

7. An application of the polyamide 12 / modified boron nitride composite powder as claimed in claim 6, characterized in that: Powder materials for selective laser sintering.

Citation Information

Patent Citations

  • Preparation method of polyamide microsphere

    CN111171345A

  • Nylon powder for 3D printing and preparation method thereof

    CN116355397A